ENTREPRENEURIAL COMPETENCIES AND THEIR EFFECT ON SME GROWTH IN ENUGU METROPOLIS - Eze , Ngozi Amarachi; Nwosu, Uchenna Obiora (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
The study evaluated the effect of entrepreneurial skills on the performance of small and medium enterprises in Enugu state. The specific objective was to: examine the effect of leadership skills on the output of SMEs and evaluate the effect of networking skills on the profits making of SMEs in Enugu metropolis. The area of the study was Enugu Metropolis. Two hundred and seventy-three (273) business owners and employees were selected for the study. The study used the descriptive survey design approach. The primary source of data was the administration of questionnaire. Two hundred and fifty-three (253) respondents returned their questionnaire and accurately filled. Data was presented and analyzed by mean score and standard deviation using Sprint Likert Scale. The hypotheses were analyzed using Z - test statistic tool. The findings indicated that Leadership skills had significant positive effect on the output of SMEs in Enugu metropolis, Z (95, n = 272), 7.034 < 9.944, P. <.05 and Networking skills had significant positive effect on the profits making of SMEs in Enugu metropolis, Z(95, n = 272), 7.034 < 9.944, P. <.05. The study concluded that Leadership skills and Networking skills had significant positive effect on the output and profits making t of SMEs in Enugu metropolis. The study recommended among others that the owners or management of the small and medium enterprises should provide direction and vision, motivate and inspire others, and help create an environment conducive to success by promoting communication and collaboration among team members